2003
DOI: 10.1353/eas.2003.0001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Business Skills Cognition: The Case of Informal Sector Entrepreneurs in Kenya

Abstract: There has been an increased interest in informal sector business activities. One of the major concerns has been the cognitive abilities of the participants of this sector, especially in view of the liberalised and highly competitive nature of business operations today. This paper presents and discusses findings of a study on measuring Business Skills Cognition among informal sector business owners. Data were collected from 208 respondents distributed over nine trading centres in both urban and rural Ken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…One of the major problems in social science research is the measurement of human behaviour or behavioural attributes with accuracy (Bosire & Gamba, 2003). Yet, accuracy is a vital component in scientific research.…”
Section: Validity and Reliability Of Instrumentmentioning
confidence: 99%
“…One of the major problems in social science research is the measurement of human behaviour or behavioural attributes with accuracy (Bosire & Gamba, 2003). Yet, accuracy is a vital component in scientific research.…”
Section: Validity and Reliability Of Instrumentmentioning
confidence: 99%
“…In their study on measuring business skills cognition among informal sector business owners, Bosire and Gamba (2003) found that informal sector business owners differ in the various dimensions of business and in business skills cognition. The findings of their study conform to the view that knowledge is a very powerful tool in many respects, and spheres of modern living.…”
Section: Mean Scoresmentioning
confidence: 99%
“…O que não é verdade, visto que os mercados informais são encontrados em diversos lugares do planeta, embora em maior concentração nos países em desenvolvimento, e neles, comumente, se encontram estruturas tipológicas de marketing muito semelhantes ou até iguais ao marketing informal (e.g., Peña, 1999;Bosire & Gamba, 2003;Sridharan & Viswanathan, 2008;Viswanathan et al, 2009;Fiess, Fugazza & Maloney, 2010;Viswanathan, Yassine & Clarke, 2011;Steel, 2012;Lauermann, 2013;Ozuduru, Varol & Ercoskum, 2014) 2012) observaram que em mercados de subsistência, microempreendedores tentavam melhorar seus desempenhos em termos de negócio a partir de acessibilidade e compensações, estabelecendo cocriação de valor, utilizando de interações informais cara-a-cara e redes sociais, com características de empatia e engodo. E mais recentemente, no Peru, Stell (2012) estudou as oportunidades de negócios no setor de turismo para pessoas desempregadas, que por causa da necessidade, tornam-se vendedores ambulantes.…”
Section: Discussão E Considerações Finaisunclassified
“…O propósito principal desses microempreendedores é sobressair-se em relação aos seus concorrentes com vantagens competitivas sustentáveis, por meio de estratégias idiossincráticas de marketing e vendas, em formato intuitivo, improvisado e de baixo custo. O indivíduo desenvolve estas estratégias no momento em que as realiza, com base em experiências anteriores e em seu cotidiano, de modo totalmente experimental (Bosire & Gamba, 2003;Souza et al, 2013). Nesse desenvolvimento de estratégias, ocorre uma série de processos psicossociais influenciados pelo ambiente social e mercadológico em inserção, pela cultura e pela natureza de sobrevivência, que potencializam em um indivíduo características empreendedoras de proatividade e inovação (Mueller & Thomas, 2001;Harrison & Leitch, 2005;Pimentel, 2007;Pedroso, Massukado-Nakatani & Mussi, 2009).…”
Section: Introductionunclassified